Cultural Citizenship: Definitions and Empirical Contextualization - Ivanov, Danila; Vlasova, Tat'yana; Abramov, Roman (Sotsiologicheskoe Obozrenie / Russian Sociological Review, 2024)
The article develops an approach to the conceptualization of “cultural citizenship”, which is used to describe the issues of overcoming cultural differences in the process of integration and social inclusion. Cultural citizenship is one of the concepts that develop the paradigms of citizenship and civic consciousness that exist in the tradition of political theory and sociology of culture. The purpose of the article is to develop a sociological approach to “cultural citizenship”, based on such existing family concepts as citizenship (membership), solidarity, identity. The first part of the article compares the legal and sociological interpretations of citizenship and their relationship with the cultural aspect of citizenship. In the second part, based on this comparison, the subject and central problems of cultural citizenship in the social sciences are formulated. In the third part, two approaches to the definition of cultural citizenship are analyzed. The first approach leans towards political theory and defines the state as a source of citizenship, focusing on legal instruments of integration. The second leans towards cultural sociology and defines community as a source of citizenship, focusing on integrative practices of cultural production. The analysis of the two approaches in the final part actualizes the empirical study of cultural citizenship as a process implemented at the organizational level. Cultural citizenship, in this vein, is defined as the process of two-sided inclusion of ‘strange’ and ‘different’ cultural traits of dominant and minoritarian social category with respect to the integrity of the dominant cultural variation. The main operationalization of the organizational level finds itself in “cultural institutions” (e.g., exposition halls, museums, libraries, etc.) that are supposed to play a key role in the cultural citizenship process.